Cu and Zn in selected tissues of Monopterus albus, asian swamp eel from paddy cultivation areas of Tumpat, Kelantan. - Sow, Ai Yin; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir (2012)
The main objective of this study is to determine the concentrations of Zn and Cu in selected tissues (liver, muscle and skin) of Asian swamp eel (Monopterus albus) collected from paddy cultivation in Kelantan State (Malaysia). Among these tissues, Zn and Cu were found to be the highest in liver with mean concentrations of 98.48 ± 8.47 μg/g and 7.68 ± 1.36 μg/g, respectively. In contrast, Zn and Cu were found to be the lowest in the muscle with the mean concentrations of 48.79±18.30 μg/g and 0.65±0.43 μg/g, respectively. An insignificant difference (p>0.05) was showed by comparing Zn concentration in the eel liver for the ploughing months of March, April and May. Similar trend was obtained for Zn and Cu concentrations in skin of the same period, respectively. By comparing with the safety guidelines of Canadian Food Standard (Cu: 100 μg/g; Zn: 100 μg/g) and Hungarian Standard (Cu: 60 μg/g; Zn; 80 μg/g), the edible parts (muscle and skin) of swamp eel were below the maximum permissible limits. The findings of this study indicate that M. albus collected from paddy cultivation in Kelantan were less contaminated by pesticide- and fertilizer-originated pollutants. The edible parts of M. albus also are safe for consumption by human beings.